OPTIMIZATION OF MSMES PROMOTION OF TAPIS LAMPUNG THROUGH SOCIAL COMMERCE IN DIGITAL MEDIA - Wulan Suciska; Anna Gustina Zainal; Nanang Trenggono; Vito Frasetya; Feri Firdaus; Emirullyta Harda Ninggar; Puspandari Setyowati Sugiyanto (Bajang Institute, 2022)
The Covid-19 pandemic has had an impact on the business world, but the most affected are micro, small, and medium enterprises that have limitations in terms of resources. Including Lampung tapis MSMEs in Katon State Village which experienced a 70% decrease in turnover. Micro, small and medium enterprises must be able to take advantage of their limited digital resources to be able to increase sales. One way that can be done is to use social commerce on several social media platforms as a means of promotion as well as sales. The purpose of this community service activity is to help the people of Katon State village to use social commerce as an alternative medium to promote their Tapis cloth products so that people can find out about Tapis fabric products and finally buy the Tapis fabric products. This training provides an understanding of the use of social commerce on four social media, namely Whatsapp, Facebook, Instagram, and TikTok. As a result, 96.7% of the 60 training participants admitted that the use of social commerce for promotion would be very beneficial in the sale of Lampung tapis.